Patient satisfaction with nursing services - Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 1998)
In the past the evaluation of the quality of health care was based mainly on health professional’s views. Nowadays, there is agreement that patient satisfaction represents an important index of the quality of health services. Patient satisfaction from nursing care has a special meaning since nurses represent the majority of health professionals and they provide bedside care. In the literature most of the authors agree that nursing care is the most important factor contributing to the total patient satisfaction with hospital services. The basic findings of this literature review were that most of the studies had methodological problems, they used instruments developed years ago or/and without proper psychometric properties.